Preparation for Grace in Puritanism: An Evaluation from the Perspective of Reformed Anthropology - Hendra Thamrindinata (Diligentia: Journal of Theology and Christian Education, 2019)
The Puritans’ doctrine on the preparation for grace, whose substance was an effort to find and to ascertain the true marks of conversion in a Christian through several preparatory steps which began with conviction or awakening, proceeded to humiliation caused by a sense of terror of God’s condemnation, and finally arrived into regeneration, introduced in the writings of such first Puritans as William Perkins (1558-1602) and William Ames (1576-1633), has much been debated by scholars. It was accused as teaching salvation by works, a denial of faith and assurance, and a divergence from Reformed teaching of human's total depravity. This paper, on the other hand, suggesting anthropology as theological presupposition behind this Puritan’s preparatory doctrine, through a historical-theological analysis and elaboration of the post-fall anthropology of Calvin as the most influential theologian in England during Elizabethan era will argue that this doctrine was fit well within Reformed system of believe.